Thiadiazolidinone-8 ameliorates inflammation associated with experimental colitis in mice - Mateus, Vanessa (2018)
Thiadiazolidinone-8 (TDZD-8) is an effective thiadiazolidinone derivate that is able to suppress the expression of inflammatory cytokines; it also presents tissue protective actions by glycogen synthase kinase (GSK)-3β inhibition, promoting thus an anti-inflammatory effect. Since inflammatory bowel disease is a chronic disease with reduced quality of life, where currently available therapies are only able to induce or maintain the patient in remission, it is crucial to investigate new pharmacological approaches. The main objective of this study was to evaluate the effect of TDZD-8 in 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced colitis. Male CD-1 mice with TNBS-induced colitis were treated with a daily dose of TDZD-8 5 mg/kg/day IP for 4 days. The anti-inflammatory properties of TDZD-8 in the TNBS-induced colitis were confirmed by suppression of pro-inflammatory mediators, such as tumor necrosis factor (TNF)-α, interleukin (IL)-1β and myeloperoxidase, as well as by the significant increase of the anti-inflammatory cytokine, IL-10. These treated mice also presented a reduction in fecal hemoglobin and alkaline phosphatase, suggesting a beneficial effect of TDZD-8. Furthermore, renal and hepatic biomarkers remained stabilized after treatment. In conclusion, TDZD-8 reduces the inflammatory response associated with TNBS-induced colitis in mice, and modulation of GSK-3β seems to be an interesting pharmacological target in colitis.